Endoglin and Systemic Sclerosis: A PRISMA-driven systematic review - Grignaschi, Silvia; Sbalchiero, Anna; Spinozzi, Giuseppe; Palermo, Bianca Lucia; Cantarini, Claudia; Nardiello, Chantal; Cavagna, Lorenzo; Olivieri, Carla (Frontiers in Medicine, 2022)
Background: Systemic Sclerosis (SSc) is a rare autoimmune disease whose pathogenesis is still poorly understood. The Transforming Growth Factor β superfamily is considered pivotal and a crucial role has been suggested for the type III receptor, Endoglin (ENG). The aim of this systematic review is to investigate and combine the current clinical and molecular available data, to suggest novel hints for further studies. Methods: We followed PRISMA guidelines; the search was performed on three databases (MEDLINE, Web of Science, Embase) in date November 2nd, 2021. Subsequent to the exclusion of duplicates, we applied as inclusion criteria: 1. focus on the relationship between ENG and SSc; 2. English language. As exclusion criteria: 1. ENG exclusively as a cellular biomarker; 2. no focus on ENG-SSc relationship; 3. review articles and 4. abstracts that did not add novel data. Eligibility was assessed independently by each author to reduce biases. We divided records into clinical and molecular works and subgrouped them by their study features and aim. Results: We selected 25 original papers and 10 conference abstracts. Molecular studies included 6 articles and 4 abstracts, whereas clinical studies included 17 articles and 6 abstracts; 2 articles presented both characteristics. Molecular studies were focussed on ENG expression in different cell types, showing an altered ENG expression in SSc-affected cells. Clinical studies mainly suggested that different disease phenotypes can be related to peculiar disregulations in soluble ENG concentrations. Discussion: Concerning the possible limits of our search, boolean operators in our strings might have been uneffective. However, the use of different strings in different databases should have reduced this issue at a minimum. Another bias can be represented by the selection step, in which we excluded many articles based on the role of Endoglin as a histological vascular marker rather than a signaling receptor. We tried to reduce this risk by performing the selection independently by each author and discussing disagreements. Our systematic review pointed out that ENG has a pivotal role in activating different TGFβ-stimulated pathways that can be crucial in SSc pathogenesis and progression.